Infertility rates following POMB/ACE chemotherapy for male and female germ cell tumours – a retrospective long-term follow-up study - Gaffan, J (Nature Publishing Group, 2003)
The risk of chemotherapy-induced infertility in male and female germ cell tumour (GCT) survivors is unclear, but may correlate with cisplatin dose. Here, we examine a large series of GCT patients for the effect of chemotherapy on those attempting to have children. Our GCT database was screened for nonseminomatous GCT patients who had (1) received POMB/ACE chemotherapy (cisplatin, vincristine, methotrexate, bleomycin alternating with actinomycin D, cyclophosphamide and etoposide) and (2) stage I male GCT patients who were untreated between 1977 and 1996. Fertility was assessed by questionnaire and medical records. A total of 64 of 153 treated and 35 of 115 untreated men attempted to have children. In all, 28% (18 out of 64) receiving POMB/ACE were unsuccessful. Radiotherapy (six), atrophic remaining testis (one) or prior infertility (three) were implicated in 10 cases, so chemotherapy-induced infertility may have occurred in only 11% (eight out of 64). Strikingly, 26% (nine out of 35) of untreated stage I patients also failed to have children (three had radiotherapy, three prior infertility). Moreover, in treated men, no association was seen between cisplatin dose and infertility. In contrast, radiotherapy significantly increased male infertility (P=0.001). Of 28 treated women who attempted to have children, 25% (seven out of 28) were unsuccessful. One previously had infertility and one subsequently had successful IVF so chemotherapy-induced infertility potentially occurred in only 18% (five out of 28) and was not related to cisplatin dose. In conclusion, the risk of chemotherapy-induced infertility is low in both male and female GCT patients and does not clearly correlate with the cumulative cisplatin dose.